A Study of Methotrexate Alone vs HCQ Combination with Methotrexate in DMARD-Naïve Patients with Early Rheumatoid Arthritis - Sarfraz, Wajiha; Sarfraz, Zainab; Iqbal, Umar; Haq, Arshaman Ul (Biological and Clinical Sciences Research Journal, 2025)
Early and effective disease control in rheumatoid arthritis (RA) is crucial to prevent joint damage and long-term disability. Methotrexate (MTX) remains the cornerstone DMARD; however, combination therapy with Hydroxychloroquine (HCQ) is often considered to enhance efficacy. Objective: To compare the effectiveness of Methotrexate alone versus a combination of Methotrexate and Hydroxychloroquine in achieving disease control in patients with early RA. Methodology: This quasi-experimental study was conducted at CMH Lahore from October 22 to December 31, 2024. A total of 225 patients with early RA were enrolled and divided into two groups: Group A received Methotrexate monotherapy (15–25 mg/week), and Group B received Methotrexate in combination with Hydroxychloroquine (200–400 mg/day). Disease Activity Score using 28-joint count and ESR (DAS28-ESR) was recorded at baseline and 10 weeks. Results: The mean baseline DAS28-ESR score was comparable between groups (Group A: 5.82 ± 0.91 vs. Group B: 5.87 ± 0.85, p = 0.63). After 10 weeks, a significantly greater reduction in disease activity was observed in the combination group (Group A: 4.12 ± 0.74 vs. Group B: 3.38 ± 0.65, p < 0.001). Remission or low disease activity was achieved in 42.7% of Group A and 64.4% of Group B (p = 0.002). Adverse events were mild and similar between groups. Conclusion: The combination of Methotrexate and Hydroxychloroquine is significantly more effective than Methotrexate alone in reducing disease activity in early RA, with a comparable safety profile. Early combination therapy may provide a more robust and timely response in disease control.